Ketamine in affective disorders - expectations and limitations - Ewelina Soroka; Dorota Adamczyk; Katarzyna Adamczyk; Urszula Fałkowska; Marcin Olajossy (Kazimierz Wielki University, 2019)
Classified as dissociative psychedelic, ketamine is a psychoactive agent whose exact mechanism of action has not been fully elucidated. In human and veterinary medicine ketamine is administered during preoperative analgesia. In anesthesiology it is employed either during induction of complex anesthesia or rarely, as a mono-anesthetic agent implemented in short-time procedures that do not cause visceral pain. Hallucinations, nausea, vomiting and elevation of systemic and intracranial pressure may be listed among adverse drug reactions limiting the use of ketamine. Ketamine is believed to exert antidepressant effects by antagonizing N-Methyl-D-aspartate receptor (NMDAR), combined with its presumptive inhibitory action on noradrenaline and serotonin transporter. Unlike other antidepressants, requiring weeks to exert apparent effects, ketamine relieves depressive symptoms within hours from administration. First reports on ketamine efficacy in the treatment of depressive episode come from 2000. The use of ketamine appears to be beneficial in patients who have exhausted other possible pharmacotherapeutic options. Current data suggest that single ketamine infusion is suitable for patients with treatment-resistant unipolar or bipolar depression without psychotic features, and with no previous history of psychoactive substance abuse. The prospective therapeutical applications of ketamine in the treatment of affective disorders are promising, however, further comprehensive research is still required.